ΔPKC interaction with the d subunit of F1Fo ATP synthase impairs energetics and exacerbates ischemia/reperfusion injury in isolated rat hearts. (December 2015) - Walker, Matthew; Caldwell, Robert W.; Yoon, Yisang; Nguyen, Tiffany T.; Johnson, John A.
Abstract: Previously, we demonstrated protection against hypoxic injury in neonatal cardiac myocytes and reduced release of cardiac troponin I from perfused rat hearts by a novel peptide inhibitor [NH2 -YGRKKRRQRRRMLATRALSLIGKRAISTSVCAGRKLALKTIDWVSFDYKDDDDK-] of the delta protein kinase C (δPKC) interaction with the "d" subunit of mitochondrial F1 Fo ATP synthase (dF1 Fo). This peptide was developed in our laboratory and contains: an HIV-Tat protein transduction domain; a mitochondrial targeting motif; the δPKC-dF1 Fo inhibitor sequence; and a FLAG epitope. In the present study the δPKC-dF1 Fo inhibitor attenuated co-immunoprecipitation of δPKC with dF1 Fo, improved recovery of contractility, diminished levels of tissue t-carbonyls and 4-hydroxy-2-nonenal (HNE), and reduced 2, 3, 5-triphenyltetrazolium chloride-monitored infarct size following simulated global ischemia/reperfusion (IR) exposures. Perfusion of hearts with this peptide prior to IR enhanced ATP levels 2.1-fold, improved ADP (state 3)- and FCCP (maximal)-stimulated respiration in mitochondrial oxygen consumption assays, and attenuated Ca ++ -induced mitochondrial swelling following ischemic injury. Mitochondrial membrane potential (assessed by JC-1) was also improved 1.6-fold by the inhibitor in hearts subsequently exposed to IR injury. Brief IR exposures did not cause mitochondrial loss of cytochrome c in the presence or absence of the inhibitor. Additionally, the inhibitor did not modify accumulation of the autophagy marker LC3II after brief IR injury. Our results support the potential for this first-in-class peptide as a translational agent for combating cardiac IR injury. Highlights: Cardiac ischemia/reperfusion (IR) injury claims a life ~ every 40 s. Energy deprivation plays an important role in IR injury. δPKC inhibits F1 Fo ATP synthase, the enzyme responsible for ~ 90% of cardiac ATP. A novel peptide blocks this interaction and protects rat hearts. This peptide may have potential as a therapeutic in heart attacks.